Antecedent and Consequence Model of Trust on Online Fashion Retail (Zalora) - Laili, Fauzia Nur; Wahyudi, Lilik (International Journal of Science and Applied Science: Conference Series, 2021)
This study has the purpose to understand the antecedents and consequences of trust in online shopping consumers. The model of three (perceived quality, perceived risk, and trust) increase the intention to purchase on the e-commerce platform. "Zalora" as one of the most popular fashion online in Asia has strategies to get their consumer's trust. This study is quantitative research using an online survey method. We share the link address of the survey using social media Whatsapp. We screened the questionnaire that had been filled by 372 respondents and we choose 238 respondents who met the requirements. In this study we use 4 variables perceived quality, perceived risk, trust, and intention to purchase. The results of this study indicate that perceived quality negatively affected perceived risk (-0.277). Perceived risk also negatively affected trust (-0.193). Meanwhile, perceived quality directly has a positive effect on trust (0.726) and trust has a positive effect on the intention to purchase on the Zalora eCommerce platform.